The re-use atlas : a designer's guide towards a circular economy - Baker-Brown, Duncan (RIBA Publishing, 2017)
"This book is a highly illustrated 'atlas', taking the reader on a journey via four distinct 'steps' (recycling, reuse, reduce, closed loop), from a linear economy towards a system emulating the natural world - a circular economy. Featuring over 20 detailed case studies describing design exemplars from the worlds of textile and fashion design, product design, interior architecture, architecture and urban design, this book's purpose is to show designers how they can successfully navigate and exploit the emerging field of resource management and the circular economy. Each step is supplemented with an in-depth interview with an expert who is successfully tackling one or more of these challenges that face all designers today and includes contributory essays from, among others, Professor Walter Stahel of the Product-Life Institute, and Professor Jonathan Chapman, author of Emotionally Durable Design."--Cover.